Labor supply heterogeneity and demand for child care of mothers with young children - Patricia Apps; Jan Kabatek; Ray Rees; Arthur van Soest (Institute for the Study of Labor (IZA), 2012)
This paper introduces a static structural model of hours of market labor supply, time spent on child care and other domestic work, and bought in child care for married or cohabiting mothers with pre-school age children. The father's behavior is taken as given. The main goal is to analyze the sensitivity of hours of market work, parental child care, other household production and formal child care to the wage rate, the price of child care, taxes, benefits and child care subsidies. To account for the non-convex nature of the budget sets and, possibly, the household technology, a discrete choice model is used. The model is estimated using the HILDA dataset, a rich household survey of the Australian population, which contains detailed information on time use, child care demands and the corresponding prices. Simulations based on the estimates show that the time allocations of women with pre-school children are highly sensitive to changes in wages and the costs of child care. A policy simulation suggests that labor force participation and hours of market work would increase substantially in a fiscal system based solely on individual rather than joint taxation.
Keywords: J22; J13; H24; 330; time use; income tax; child care subsidies; Mütter; Weibliche Arbeitskräfte; Arbeitsangebot; Kinderbetreuung; Zeitverwendung; Schätzung; Australien